Control design of a four-terminal thyristor converter system - Oni Oluwafemi Emmanuel; Somefun Tobiloba; Longe Omowunmi Mary (E3S Web of Conferences, 2025)
The growing need for efficient long-distance power transmission and large-scale integration of renewable energy has accelerated the development of multiterminal high-voltage direct current (MTHVDC) systems. This study examines a +500 kV four-terminal Line-Commutated Converter (LCC)-based monopolar MTHVDC system as a solution for bulk power transfer and grid interconnection. The system’s capability to dynamically regulate power flow across multiple terminals is analysed using PSCAD simulations under varying current order conditions. Results highlight the influence of rectifier firing angle variations (2°–15°) and inverter conduction angle fluctuations (140°–150°) on system stability. Observed transient voltage ripples, caused by inverter extinction angle oscillations, underscore the need for advanced filtering techniques. Findings emphasize the importance of semiconductor advancements in mitigating commutation failures and harmonic distortions, particularly in weak AC grids with high renewable energy penetration. Future research should refine real-time control strategies and enhance the robustness of MTHVDC systems for improved reliability in large-scale transmission networks.